Efficacy of Sulfamethoxypyridazine in a Murine Model of Pneumocystis carinii Pneumonia - Bartlett, Marilyn S. (American Society for Microbiology, 1998)
Sulfamethoxazole is the component of co-trimoxazole responsible for its efficacy against Pneumocystis carinii pneumonia, but this drug is associated with frequent adverse effects. Sulfamethoxypyridazine is significantly more effective than sulfamethoxazole against a murine model of P. carinii and might be a candidate for testing in infected patients.